Protective film for battery cell, preparation method of protective film and lithium ion battery
By using polyester polymer and gas-phase silica protective film on the battery cell of lithium-ion batteries, the gas generated by the battery cell is absorbed, and the problems of corrosion and expansion deformation of the battery shell are solved, and the circulation and safety performance of the battery are improved.
Patent Information
- Application Number
- CN202411827975.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-25
AI Technical Summary
The gases generated during the decomposition, overcharging, overdischarge and storage of lithium-ion batteries cause corrosion and expansion deformation of the battery shell, affecting circulation and safety performance.
A cell protection film including polyester polymer and doped gas-phase silica is used. The gas-phase silica has adsorption holes that can absorb gas generated by the battery cell and reduce corrosion to the battery case.
By adsorbing gas, the expansion and deformation problems caused by excessive internal gas production of the battery are improved, the circulation and safety performance of the battery are improved, and the battery structure is simplified and the volume is miniaturized.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a protective film for a battery cell, a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries mainly include a shell, a battery cell and a protective film. The protective film and the battery cell are placed inside the shell, and the protective film is used to wrap the outer surface of the battery cell. During the assembly process of lithium-ion batteries, the protective film can shape the battery cell to facilitate the installation of the battery cell into the shell. At the same time, the protective film also protects the battery cell to prevent damage when the battery cell is installed into the shell.
[0003] In the related technology, battery cells may generate gases such as carbon monoxide, hydrogen, hydrofluoric acid, methyl chloride, phosphorus pentafluoride, etc. during formation, overcharging, over-discharging and storage. Among them, hydrofluoric acid and phosphorus pentafluoride are highly corrosive and may corrode the battery casing during battery use, increasing the risk of battery leakage. At the same time, the generated gases can easily cause the battery to expand and deform, affecting the battery's cycle performance and safety performance. Summary of the invention
[0004] The embodiments of the present invention provide a protective film for a battery cell, a preparation method thereof, and a lithium-ion battery, which can improve the technical problem that the battery cell generates gas during formation, overcharging, overdischarging, and storage processes, thereby affecting the cycle performance and safety performance of the battery.
[0005] In a first aspect, an embodiment of the present invention provides a protective film for a battery cell, the protective film comprising a polyester polymer and fumed silica doped in the polyester polymer.
[0006] In one embodiment, in the protective film, the mass percentage of the fumed silicon dioxide is 2%-4%; and / or
[0007] The thickness of the protective film is 0.15mm-0.2mm.
[0008] In one embodiment, the fumed silica has adsorption pores, and the pore diameter of the adsorption pores is 4nm-20nm; and / or
[0009] The average particle size of the fumed silica is 10 nm to 25 nm.
[0010] In a second aspect, an embodiment of the present invention provides a method for preparing the protective film as described above, the method comprising the following steps:
[0011] The fumed silica and the polyester polyol compound are stirred uniformly to obtain a mixture;
[0012] Adding an isocyanate compound to the mixture and stirring evenly to obtain a prepolymer;
[0013] adding a chain extender to the prepolymer to carry out a cross-linking reaction to obtain an intermediate;
[0014] The intermediate is pressurized and vulcanized to obtain the protective film, which includes a polyester polymer and the fumed silica doped in the polyester polymer.
[0015] In one embodiment, the polyester polyol compound includes at least one of polyethylene terephthalate and polyoxypropylene glycol; and / or
[0016] The isocyanate compound includes at least one of toluene diisocyanate and diphenylmethane diisocyanate; and / or
[0017] The chain extender includes at least one of 3,3'-dichloro-4,4'-diaminodiphenylmethane and dimethylthiotoluene diamine.
[0018] In one embodiment, in the step of uniformly stirring the fumed silica and the polyester polyol compound to obtain a mixture, the mass ratio of the fumed silica to the polyester polyol compound is (1:6)-(2:3), and / or the stirring time is 2h-4h, and / or the stirring temperature is 20°C-30°C, and / or the stirring speed is 4000rpm-6000rpm; and / or
[0019] After the step of uniformly stirring the fumed silica and the polyester polyol compound, a vacuum dehydration treatment is further included, wherein the vacuum degree of the vacuum dehydration is 0.085 MPa-0.1 MPa, and / or the time of the vacuum dehydration is 2 h-5 h.
[0020] In one embodiment, in the step of adding the isocyanate compound to the mixture and stirring evenly to obtain a prepolymer, the mass ratio of the isocyanate compound to the polyester polyol compound is (1:3)-(1.5:1), and / or the stirring time is 1h-3h, and / or the stirring temperature is 70°C-90°C; and / or
[0021] After the step of adding the isocyanate compound to the mixture and stirring evenly, a degassing treatment is further included, wherein the temperature of the degassing treatment is 20° C.-25° C., and / or the time of the degassing treatment is 30 min-60 min.
[0022] In one embodiment, in the step of adding the chain extender to the prepolymer to carry out a cross-linking reaction to obtain an intermediate, the mass ratio of the chain extender to the prepolymer is (1:500)-(1:100), and / or the temperature of the cross-linking reaction is 120°C-150°C, and / or the time of the cross-linking reaction is 5h-10h.
[0023] In one embodiment, in the step of pressurizing and vulcanizing the intermediate to obtain the protective film, the temperature of the pressurizing and vulcanizing is 110° C.-130° C., and / or the time of the pressurizing and vulcanizing is 5 min-20 min, and / or the pressure of the pressurizing and vulcanizing is 20 Pa-30 Pa; and / or
[0024] After the step of pressurizing and vulcanizing the intermediate, an aging treatment is further included, wherein the aging treatment temperature is 20° C.-30° C., and / or the aging treatment time is 5 days-8 days.
[0025] In a third aspect, an embodiment of the present invention provides a lithium-ion battery, comprising the protective film as described above or the protective film prepared by the preparation method as described above.
[0026] In one embodiment, the lithium-ion battery further includes a battery core, and the protective film is coated on the outer surface of the battery core.
[0027] Beneficial effects of the embodiments of the present invention:
[0028] In an embodiment of the present invention, the protective film for the battery cell includes a polyester polymer and fumed silica doped in the polyester polymer. On the one hand, the fumed silica has adsorption holes for gas adsorption. The fumed silica in the protective film can adsorb the gas generated by the battery cell during formation, overcharging, overdischarging and storage, reduce the corrosion of the battery shell by the gas, and improve the problem of battery expansion and deformation caused by excessive internal gas production, thereby improving the battery's cycle performance and safety performance; at the same time, the content of silicon dioxide (SiO2) in the fumed silica is not less than 99.8%. Compared with ordinary silica fillers, the impurity content in the fumed silica is less, which can reduce the impurity content in the protective film, thereby reducing the impact of impurities on the electrochemical performance of the battery cell. On the other hand, the fumed silica is doped in the polyester polymer of the protective film, and there is no need to set up a separate component of the fumed silica for storage in the battery. While adsorbing the gas, it is conducive to simplifying the structure of the battery and miniaturizing the battery volume. In addition, fumed silica has high mechanical strength, and the surface of fumed silica contains abundant siloxy groups and silanol groups, which can form hydrogen bonds with carboxyl groups, hydroxyl groups and other groups in polyester polymers, thereby enhancing the interfacial bonding force between polyester polymers and fumed silica and the interaction force between polyester polymer molecular chains, thereby improving the overall mechanical properties and adsorption properties of the protective film. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention. In the present invention, unless otherwise specified, the directional words used, such as "upper" and "lower", generally refer to the upper and lower parts of the device in actual use or working state; while "inside" and "outside" refer to the outline of the device.
[0030] In the related technology, battery cells generate gas during formation, overcharging, over-discharging and storage, which affects the cycle performance and safety performance of the battery and needs further improvement.
[0031] In order to solve the above problems, an embodiment of the present application provides a protective film for a battery cell, wherein the protective film includes a polyester polymer and fumed silica doped in the polyester polymer.
[0032] In this embodiment, the protective film for the battery cell includes a polyester polymer and fumed silica doped in the polyester polymer. On the one hand, the fumed silica has adsorption holes for gas adsorption. The fumed silica in the protective film can adsorb the gas generated by the battery cell during formation, overcharging, overdischarging and storage, reduce the corrosion of the battery shell by the gas, and improve the problem of battery expansion and deformation caused by excessive internal gas production, thereby improving the battery's cycle performance and safety performance; at the same time, the content of silicon dioxide (SiO2) in the fumed silica is not less than 99.8%. Compared with ordinary silica fillers, the impurity content in the fumed silica is less, which can reduce the impact of impurities on the electrochemical performance of the battery cell. On the other hand, the fumed silica is doped in the polyester polymer of the protective film, and there is no need to set up a separate component of the fumed silica for storage in the battery. While adsorbing the gas, it is conducive to simplifying the structure of the battery and miniaturizing the battery volume. In addition, fumed silica has high mechanical strength, and the surface of fumed silica contains abundant siloxy groups and silanol groups, which can form hydrogen bonds with carboxyl groups, hydroxyl groups and other groups in polyester polymers, thereby enhancing the interfacial bonding force between polyester polymers and fumed silica and the interaction force between polyester polymer molecular chains, thereby improving the overall mechanical properties and adsorption properties of the protective film.
[0033] In one embodiment, the pore size of the adsorption pore is 4nm-20nm. Optionally, the pore size of the adsorption pore can be any one of 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 17nm, 20nm, etc. or a range between any two. In the present invention, if the pore size of the adsorption pore is too large, it is easy to cause the mechanical strength of the protective film to decrease, and the protective film is prone to deformation or rupture when subjected to external force; if the pore size of the adsorption pore is too small, it is easy to cause the adsorption capacity and adsorption rate of the protective film to decrease, and the effect of the protective film on adsorbing gas is not ideal.
[0034] In one embodiment, the average particle size of the fumed silica is 10nm-25nm. Optionally, the average particle size of the fumed silica can be any one of 10nm, 12nm, 14nm, 18nm, 20nm, 22nm, 25nm, etc. or a range between any two. In the present invention, if the average particle size of the fumed silica is too small, it is easy to cause the fumed silica particles to agglomerate in the polyester polymer, and the effect of uniform dispersion of the fumed silica particles in the polyester polymer is not ideal; if the average particle size of the fumed silica is too large, it is easy to cause the flatness of the protective film to deteriorate, and the protective film is easily damaged under the action of external impact.
[0035] In one embodiment, the thickness of the protective film is 0.15mm-0.2mm. Optionally, the thickness of the protective film can be any one of 0.15mm, 0.16mm, 0.17mm, 0.18mm, 0.19mm, 0.2mm, etc. or a range between any two. In the present invention, if the thickness of the protective film is too large, it is easy to increase the weight of the battery and reduce the energy density. At the same time, if the thickness of the protective film is too large, the diffusion path of ions in the active material will become longer, increase the internal resistance of the battery, and cause more heat to be generated during the battery charging and discharging process, thereby reducing the battery charging and discharging efficiency; if the thickness of the protective film is too small, it is easy to cause the protective film to withstand high temperature or pressure. The effect is not ideal, and the protective film is prone to melting, shrinking, etc. under high temperature or pressure, which reduces the voltage consistency and cycle performance of the battery.
[0036] In one embodiment, in the protective film, the mass percentage of fumed silica is 2%-4%. Optionally, the mass percentage of fumed silica can be any one of 2%, 2.3%, 2.5%, 2.8%, 3%, 3.4%, 3.8%, 4%, etc., or a range between any two. In this embodiment, if the mass percentage of fumed silica is too large, it is easy to cause agglomeration of fumed silica in the polyester polymer, and the effect of uniform dispersion of fumed silica in the polyester polymer is not ideal, which reduces the mechanical strength of the protective film; if the mass percentage of fumed silica is too small, it is easy to reduce the gas adsorption effect of the protective film, and at the same time, the effect of improving the mechanical strength of the protective film is not ideal.
[0037] The present application also provides a method for preparing the protective film as described above, comprising the following steps:
[0038] S1, stirring the fumed silica and the polyester polyol compound uniformly, and vacuum dehydrating to obtain a mixture;
[0039] S2, adding the isocyanate compound to the mixture, stirring evenly, and degassing to obtain a prepolymer;
[0040] S3, adding a chain extender to the prepolymer to carry out a cross-linking reaction to obtain an intermediate;
[0041] S4. The intermediate is subjected to pressure vulcanization and aging treatment to obtain a protective film, which includes a polyester polymer and fumed silica doped in the polyester polymer.
[0042] In one embodiment, the polyester polyol compound includes at least one of polyethylene terephthalate and polyoxypropylene glycol.
[0043] In one embodiment, the isocyanate compound includes at least one of toluene diisocyanate and diphenylmethane diisocyanate.
[0044] In one embodiment, the chain extender includes at least one of 3,3'-dichloro-4,4'-diaminodiphenylmethane and dimethylthiotoluene diamine.
[0045] In one embodiment, in step S1, the mass ratio of fumed silica to polyester polyol compounds is (1:6)-(2:3). Optionally, the mass ratio of fumed silica to polyester polyol compounds can be any one of 1:6, 1:3, 1:2, 2:3, etc., or a range between any two. In the present invention, if the mass ratio between fumed silica and polyester polyol compounds is too large, it is easy to cause the dispersion effect of fumed silica in polyester polyol compounds to be unsatisfactory; if the mass ratio between fumed silica and polyester polyol compounds is too small, it is easy to cause the content of fumed silica in the protective film to be too small, thereby reducing the gas adsorption effect and mechanical properties of the protective film.
[0046] In one embodiment, in step S1, the stirring time is 2h-4h, the stirring temperature is 20℃-30℃, and the stirring speed is 4000rpm-6000rpm. Optionally, the stirring time can be any one of 2h, 2.5h, 2.8h, 3h, 3.5h, 4h, etc. or a range between any two; the stirring temperature can be any one of 20℃, 22℃, 24℃, 25℃, 27℃, 30℃, etc. or a range between any two; the stirring speed can be any one of 4000rpm, 4500rpm, 5000rpm, 5500rpm, 6000rpm, etc. or a range between any two.
[0047] In one embodiment, in step S1, dehydration can be performed under a vacuum environment. Vacuum dehydration can improve the purity of polyester polyol compounds, reduce the moisture content of the mixture, improve the quality of the mixture, and ensure the polymerization reaction. In this embodiment, the vacuum degree of vacuum dehydration is 0.085MPa-0.1MPa, and the time of vacuum dehydration is 2h-5h. Optionally, the vacuum degree of vacuum dehydration can be any one of 0.085MPa, 0.087MPa, 0.089MPa, 0.09MPa, 0.094MPa, 0.098MPa, 0.1MPa, etc., or a range between any two; the time of vacuum dehydration can be any one of 2h, 2.5h, 3h, 3.5h, 4h, 5h, etc., or a range between any two.
[0048] In one embodiment, in step S2, the mass ratio of the isocyanate compound to the polyester polyol compound is (1:3)-(1.5:1). Optionally, the mass ratio of the isocyanate compound to the polyester polyol compound can be any one of 1:3, 1:2, 1:1, 1.5:1, etc. or a range between any two. In this embodiment, if the amount of the isocyanate compound added is too much, it is easy to cause incomplete reaction of the isocyanate compound, and the unreacted isocyanate compound may remain in the protective film, affecting the overall mechanical properties of the protective film; if the amount of the isocyanate compound added is too little, it is easy to cause the cross-linking density of the protective film to decrease, and the protective film is prone to produce pores and cracks, reducing the strength and toughness of the protective film.
[0049] In one embodiment, in step S2, the stirring time is 1 hour to 3 hours, and the stirring temperature is 70° C. to 90° C. Optionally, the stirring time can be any one of 1 hour, 1.5 hours, 1.8 hours, 2 hours, 2.5 hours, 3 hours, etc., or a range between any two thereof; the stirring temperature can be any one of 70° C., 72° C., 78° C., 80° C., 85° C., 90° C., etc., or a range between any two thereof.
[0050] In one embodiment, in step S2, the degassing treatment can remove bubbles in the prepolymer, improve the compactness of the prepolymer, and thus improve the flatness and mechanical properties of the protective film. In this embodiment, the temperature of the degassing treatment is 20°C-25°C, and the time of the degassing treatment is 30min-60min. Optionally, the temperature of the degassing treatment can be any one of 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, etc., or a range between any two; the time of the degassing treatment can be any one of 30min, 35min, 40min, 45min, 50min, 60min, etc., or a range between any two.
[0051] In one embodiment, in step S3, the mass ratio of the chain extender to the prepolymer is (1:500)-(1:100). Optionally, the mass ratio of the chain extender to the prepolymer can be any one of 1:500, 1:400, 1:300, 1:200, 1:100, etc., or a range between any two of them.
[0052] In one embodiment, in step S3, the temperature of the cross-linking reaction is 120°C-150°C, and the time of the cross-linking reaction is 5h-10h. Optionally, the temperature of the cross-linking reaction can be any one of 120°C, 125°C, 130°C, 135°C, 140°C, 150°C, etc., or a range between any two thereof; the time of the cross-linking reaction can be any one of 5h, 6h, 7h, 8h, 9h, 10h, etc., or a range between any two thereof.
[0053] In one embodiment, in step S4, the intermediate is subjected to pressurized vulcanization treatment to further improve the firmness, pressure resistance and thermal stability of the protective film. In this embodiment, the temperature of pressurized vulcanization is 110°C-130°C, the time of pressurized vulcanization is 5min-20min, and the pressure of pressurized vulcanization is 20Pa-30Pa. Optionally, the temperature of pressurized vulcanization can be any one of 110°C, 115°C, 120°C, 125°C, 130°C, etc., or a range between any two; the time of pressurized vulcanization can be any one of 5min, 8min, 10min, 14min, 18min, 20min, etc., or a range between any two; the pressure of pressurized vulcanization can be any one of 20Pa, 22Pa, 24Pa, 26Pa, 28Pa, 30Pa, etc., or a range between any two.
[0054] In one embodiment, in step S4, the aging temperature is 20°C-30°C, and the aging time is 5 days-8 days. Optionally, the aging temperature can be any one of 20°C, 24°C, 26°C, 28°C, 30°C, etc., or a range between any two thereof; the aging time can be any one of 5 days, 5.5 days, 6 days, 6.5 days, 7 days, 7.5 days, 8 days, etc., or a range between any two thereof.
[0055] The present application also provides a lithium-ion battery, which includes the protective film as described above or the protective film prepared by the preparation method as described above.
[0056] In one embodiment, the lithium-ion battery further comprises a battery cell, and the protective film is coated on the outer surface of the battery cell. In this embodiment, the protective film is coated on the outer surface of the battery cell, and the fumed silica in the protective film can absorb the gas generated by the battery cell during formation, overcharging, overdischarging and storage, reducing the corrosion of the battery shell by the gas, and at the same time, it can improve the problem of battery expansion and deformation caused by excessive internal gas production, thereby improving the cycle performance and safety performance of the battery.
[0057] The above scheme is further described below in conjunction with specific implementation examples. The preferred embodiments of the present application are described in detail as follows:
[0058] Example 1
[0059] (1) Stirring fumed silica and polyester polyol compounds uniformly, and vacuum dehydrating to obtain a mixture; wherein the polyester polyol compound is polyethylene terephthalate, the mass ratio of fumed silica to polyester polyol compounds is 1:3, the average particle size of fumed silica is 23 nm, the pore size of fumed silica adsorption pores is 7 nm, the stirring time is 3 h, the stirring temperature is 25° C., the vacuum degree of vacuum dehydration is 0.095 MPa, and the vacuum dehydration time is 3 h.
[0060] (2) adding an isocyanate compound to the mixture, stirring evenly, and degassing to obtain a prepolymer; wherein the isocyanate compound is toluene diisocyanate, the mass ratio of the isocyanate compound to the polyester polyol compound is 1:1.5, the stirring time is 2 hours, the stirring temperature is 83°C, the stirring speed is 4500 rpm, the degassing time is 0.8 hours, and the degassing temperature is 23°C.
[0061] (3) adding a chain extender to the prepolymer to carry out a cross-linking reaction to obtain an intermediate; wherein the chain extender is dimethylthiotoluene diamine, the mass ratio of the chain extender to the prepolymer is 3:500, the temperature of the cross-linking reaction is 130° C., and the time of the cross-linking reaction is 8 hours.
[0062] (4) subjecting the intermediate to pressure vulcanization and aging treatment to obtain a protective film; wherein the pressure vulcanization temperature is 120° C., the vulcanization time is 15 min, the vulcanization pressure is 25 Pa, the aging temperature is 25° C., the aging time is 7 days, and the mass percentage of the fumed silica in the protective film is 3.0%.
[0063] Example 2
[0064] The difference between Example 2 and Example 1 is:
[0065] In step (1), the mass ratio of fumed silica to polyethylene terephthalate is 1:6, and the rest is the same as in Example 1.
[0066] Example 3
[0067] The difference between Example 3 and Example 1 is:
[0068] In step (1), the mass ratio of fumed silica to polyethylene terephthalate is 2:3, and the rest is the same as in Example 1.
[0069] Example 4
[0070] The difference between Example 4 and Example 1 is:
[0071] In step (1), the average particle size of the fumed silica is 10 nm, and the rest is the same as in Example 1.
[0072] Example 5
[0073] The difference between Example 5 and Example 1 is:
[0074] In step (1), the average particle size of the fumed silica is 25 nm, and the rest is the same as in Example 1.
[0075] Example 6
[0076] The difference between Example 6 and Example 1 is:
[0077] In step (1), the diameter of the adsorption pores of the fumed silica is 4 nm, and the rest is the same as in Example 1.
[0078] Example 7
[0079] The difference between Example 7 and Example 1 is:
[0080] In step (1), the diameter of the adsorption pores of the fumed silica is 20 nm, and the rest is the same as in Example 1.
[0081] Example 8
[0082] The difference between Example 8 and Example 1 is:
[0083] In step (1), the polyester polyol compound is polyoxypropylene glycol, the isocyanate compound is diphenylmethane diisocyanate, the chain extender is 3,3'-dichloro-4,4'-diaminodiphenylmethane, and the rest is the same as in Example 1.
[0084] Example 9
[0085] The difference between Example 9 and Example 1 is:
[0086] In step (2), the mass ratio of toluene diisocyanate to polyethylene terephthalate is 1:3, and the rest is the same as in Example 1.
[0087] Example 10
[0088] The difference between Example 10 and Example 1 is:
[0089] In step (2), the mass ratio of toluene diisocyanate to polyethylene terephthalate is 1.5:1, and the rest is the same as in Example 1.
[0090] Embodiment 11
[0091] The difference between Example 11 and Example 1 is that:
[0092] In step (1), the mass ratio of fumed silica to polyethylene terephthalate is 1:1, and the rest is the same as in Example 1.
[0093] Example 12
[0094] The difference between Example 12 and Example 1 is:
[0095] In step (1), the average particle size of the fumed silica is 5 nm, and the rest is the same as in Example 1.
[0096] Example 13
[0097] The difference between Example 13 and Example 1 is that:
[0098] In step (1), the average particle size of the fumed silica is 42 nm, and the rest is the same as in Example 1.
[0099] Embodiment 14
[0100] The difference between Example 14 and Example 1 is that:
[0101] In step (1), the diameter of the adsorption pores of the fumed silica is 22 nm, and the rest is the same as in Example 1.
[0102] Embodiment 15
[0103] The difference between Example 15 and Example 1 is that:
[0104] In step (1), the diameter of the adsorption pores of the fumed silica is 3 nm, and the rest is the same as in Example 1.
[0105] Example 16
[0106] The difference between Example 16 and Example 1 is that:
[0107] In step (2), the mass ratio of toluene diisocyanate to polyethylene terephthalate is 2:1, and the rest is the same as in Example 1.
[0108] Embodiment 17
[0109] The difference between Example 17 and Example 1 is that:
[0110] In step (1), no vacuum dehydration operation is performed, and the rest is the same as in Example 1.
[0111] Embodiment 18
[0112] The difference between Example 18 and Example 1 is that:
[0113] In step (2), no degassing operation is performed, and the rest is the same as in Example 1.
[0114] Embodiment 19
[0115] The difference between Example 19 and Example 1 is that:
[0116] In step (4), no pressure vulcanization operation is performed, and the rest is the same as in Example 1.
[0117] Comparative Example 1
[0118] The difference between Comparative Example 1 and Example 1 is:
[0119] In step (1), the mass ratio of fumed silica to polyethylene terephthalate is 0:1, and the rest is the same as in Example 1.
[0120] Test method:
[0121] (1) Mechanical properties test
[0122] The protective films prepared in Examples 1 to 19 and Comparative Example 1 were subjected to tensile strength tests and flexural strength tests, wherein the tensile strength test operation reference standard GB / T1040.1-2006, and the flexural strength test operation reference standard ISO178-93. The results are shown in Table 1 below.
[0123] Table 1
[0124]
[0125]
[0126] (II) Cyclic stability test
[0127] The protective films prepared in Examples 1 to 19 and Comparative Example 1 were coated on the outer surface of the battery cell, and the battery cell coated with the protective film was placed in an aluminum shell to make a lithium ion battery. The lithium ion battery was subjected to a cycle stability test. The test method is as follows:
[0128] In a 25°C environment, constant current charge and discharge cycles were performed at 1C (1A) current, with a voltage range of 2.0-3.65V, for 100 cycles. The maximum expansion force of the battery at the 100th cycle was recorded. The initial expansion force was 300.258kgf. The maximum expansion force data is shown in Table 2 below:
[0129] Table 2
[0130]
[0131]
[0132] According to the test results in Tables 1 and 2, the protective film for the battery cell includes a polyester polymer and fumed silica doped in the polyester polymer, which can improve the problem of battery expansion and deformation caused by excessive internal gas production, and improve the battery's cycle performance and safety performance; in addition, doping fumed silica in the polyester polymer can improve the mechanical properties of the protective film.
[0133] From the analysis of Examples 1-19 and Comparative Example 1, it can be seen that the protective film for the battery cell includes a polyester polymer and fumed silica doped in the polyester polymer. The fumed silica has adsorption pores for adsorbing gas. The fumed silica in the protective film can adsorb the gas generated by the battery cell during formation, overcharging, overdischarging and storage, thereby improving the problem of battery expansion and deformation caused by excessive internal gas production, thereby improving the battery's cycle performance and safety performance; in addition, doping fumed silica in the polyester polymer can improve the mechanical properties of the protective film.
[0134] Analysis of Examples 1-16 and Example 17 shows that vacuum dehydration of the mixture can improve the purity of the polyester polyol compounds, reduce the moisture content of the mixture, improve the quality of the mixture, and further ensure the mechanical properties of the protective film and the cycle performance of the battery.
[0135] Analysis of Examples 1-16 and Example 18 shows that after adding the isocyanate compound to the mixture, a degassing treatment is performed, which can improve the compactness of the prepolymer and further ensure the mechanical properties of the film and the cycle performance of the battery.
[0136] From the analysis of Examples 1-16 and Example 19, it can be seen that pressurized vulcanization treatment of the intermediate can further ensure the mechanical properties of the protective film and the cycle performance of the battery.
[0137] From the analysis of Examples 1-3 and Example 11, it can be seen that by controlling the mass ratio of fumed silica to polyester polyol compounds within an appropriate range, the mechanical properties and gas adsorption properties of the protective film can be further ensured.
[0138] From the analysis of Example 1, Example 4, Example 5, Example 12 and Example 13, it can be seen that controlling the average particle size of the fumed silica within an appropriate range can further ensure the mechanical properties and gas adsorption performance of the protective film.
[0139] From the analysis of Example 1, Example 6, Example 7, Example 14 and Example 15, it can be seen that the mechanical properties and gas adsorption performance of the protective film can be further ensured by controlling the pore size of the adsorption pores of the fumed silica within an appropriate range.
[0140] From the analysis of Example 1, Example 9, Example 10 and Example 16, it can be seen that controlling the mass ratio of toluene diisocyanate to polyethylene terephthalate within an appropriate range can further ensure the mechanical properties and gas adsorption properties of the protective film.
[0141] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A protective film for a battery cell, characterized in that: The protective film includes a polyester polymer and fumed silica doped in the polyester polymer.
2. The protective film according to claim 1, characterized in that: In the protective film, the mass percentage of the fumed silica is 2%-4%; and / or The thickness of the protective film is 0.15mm-0.2mm.
3. The protective film according to claim 1 or 2, characterized in that: The fumed silica has adsorption pores, and the pore diameter of the adsorption pores is 4nm-20nm; and / or The average particle size of the fumed silica is 10 nm to 25 nm.
4. A method for preparing a protective film according to any one of claims 1 to 3, characterized in that: The following steps are involved: The fumed silica and the polyester polyol compound are stirred uniformly to obtain a mixture; Adding an isocyanate compound to the mixture and stirring evenly to obtain a prepolymer; adding a chain extender to the prepolymer to carry out a cross-linking reaction to obtain an intermediate; The intermediate is pressurized and vulcanized to obtain the protective film, which includes a polyester polymer and the fumed silica doped in the polyester polymer.
5. The preparation method according to claim 4, characterized in that: The polyester polyol compound includes at least one of polyethylene terephthalate and polyoxypropylene glycol; and / or The isocyanate compound includes at least one of toluene diisocyanate and diphenylmethane diisocyanate; and / or The chain extender includes at least one of 3,3'-dichloro-4,4'-diaminodiphenylmethane and dimethylthiotoluene diamine.
6. The preparation method according to claim 4 or 5, characterized in that: In the step of uniformly stirring the fumed silica and the polyester polyol compound to obtain a mixture, the mass ratio of the fumed silica to the polyester polyol compound is (1:6)-(2:3), and / or the stirring time is 2h-4h, and / or the stirring temperature is 20°C-30°C, and / or the stirring speed is 4000rpm-6000rpm; and / or After the step of uniformly stirring the fumed silica and the polyester polyol compound, a vacuum dehydration treatment is further included, wherein the vacuum degree of the vacuum dehydration is 0.085 MPa-0.1 MPa, and / or the time of the vacuum dehydration is 2 h-5 h.
7. The preparation method according to claim 4 or 5, characterized in that: In the step of adding the isocyanate compound to the mixture and stirring evenly to obtain the prepolymer, the mass ratio of the isocyanate compound to the polyester polyol compound is (1:3)-(1.5:1), and / or the stirring time is 1h-3h, and / or the stirring temperature is 70°C-90°C; and / or After the step of adding the isocyanate compound to the mixture and stirring evenly, a degassing treatment is further included, wherein the temperature of the degassing treatment is 20° C.-25° C., and / or the time of the degassing treatment is 30 min-60 min.
8. The preparation method according to claim 4 or 5, characterized in that: In the step of adding the chain extender to the prepolymer to carry out a cross-linking reaction to obtain an intermediate, the mass ratio of the chain extender to the prepolymer is (1:500)-(1:100), and / or the temperature of the cross-linking reaction is 120°C-150°C, and / or the time of the cross-linking reaction is 5h-10h.
9. The preparation method according to claim 4 or 5, characterized in that: In the step of pressurizing and vulcanizing the intermediate to obtain the protective film, the temperature of the pressurizing and vulcanizing is 110° C.-130° C., and / or the time of the pressurizing and vulcanizing is 5 min-20 min, and / or the pressure of the pressurizing and vulcanizing is 20 Pa-30 Pa; and / or After the step of pressurizing and vulcanizing the intermediate, an aging treatment is further included, wherein the aging treatment temperature is 20° C.-30° C., and / or the aging treatment time is 5 days-8 days.
10. A lithium ion battery, characterized in that: It comprises the protective film as described in any one of claims 1 to 3 or the protective film prepared by the preparation method as described in any one of claims 4 to 9.
11. The lithium ion battery according to claim 10, characterized in that: The lithium-ion battery further comprises a battery core, and the protective film is coated on the outer surface of the battery core.
Citation Information
Cited By
Protective film, preparation method thereof and lithium ion battery
CN121439997A